Handoff delay reduction in NEMO based VANET (HDR-NV) for enhanced performance - Rahman, Shaikh Mohammad Ehsanur (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
Vehicular Ad hoc networks (VANETs) comprise of vehicle-to-vehicle and vehicle-to-infrastructure communications and can be considered the most suitable technology to enable Intelligent Transport System (ITS) application to bestow the user mobility, safety and productivity with human comfort. In vehicular environment, vehicle's fast movement introduces handoff. Handoff is the process of switching access points of mobile nodes during their movement towards the road direction. As a delay sensitive ITS application, during the VANET operation, handoff delays and packet losses are very crucial. During handoff, when mobile node (vehicle) is acquiring new care of address (CoA), packets directed toward that node are lost; because it's old identity is no more valid. So in high speed dynamic vehicular environment the number of frequent handoffs would produce delay beyond the normal limit. A complete handoff including both MAC layer, for switching between APs, and network layer, for new CoA registration and configuration, produce adaptation delay which has diverse impact to ITS application. Therefore, to resolve the issues in performance enhancement of handoff delay and packet losses during handoff in VANET environment is very important. A domain based Handoff Delay Reduction in NEMO based VANET (HDR-NV) scheme is proposed in this thesis. Number of vehicles moving towards the road, construct a domain where network mobility-basic support protocol (NEMO-BSP) is applied. A vehicle is selected as master router (MR) and connected to the road side unit (RSU) to the internet and other vehicles in the domain work as localization router (LRs) and communicate through MR. Three performance matrices: handoff latency, packet loss and inter-frame delay have been measured to evaluate the scheme. Simulation test was performed in network simulator (NS)3 and MATLAB SIMULINK to evaluate the performance. From the simulated result, it was observed that the overall achievement of handoff latency is reduced from standard 1100 ms to 653 ms and packet losses reduced by 60%. Evaluation and comparison have made with benchmark papers. During highlighting the development of scheme to reduce handoff delay and packet loss in this thesis, a significant reduced number of handoffs are identified as well.